Relationship between Perceived Teacher Support and Learning Engagement in EFL Context: The Mediating Role of Achievement Emotions - Yajun Wu; Xia Kang (International Journal of Education and Humanities, 2023)
The facilitative effect of teacher support on students’ consequential learning outcomes has been validated across student populations at all levels. However, few studies have explored the mediating mechanisms between teacher support and learning engagement, especially in English as a foreign language (EFL). The present study seeks to explore whether achievement emotions mediated the relationship between teacher support and learning engagement in learning EFL. Data were collected from 527 Chinese secondary EFL learners in Grades 7 and 8 through convenience sampling. Results of structural equation modelling (SEM) and mediation analysis showed that perceived teacher support was significantly associated with foreign language (FL) achievement emotions. FL achievement emotions, in turn, predicted learning engagement. These findings add to the evidence base for the beneficial effect of teacher support on EFL learners’ learning engagement. Implications and directions for future studies are discussed